Effectiveness of Panchavalkala Pralepa and Jalaukavacharana in Reducing Duration for Regression of Vranashopha w.s.r. to Cellulitis: A Randomized Controlled Trial (International Journal of Ayurveda and Pharma Research, 2022)
Acharya Sushruta was well aware about importance of Vranashopha (stages of abscess formation), Vrana (wound) and their management in surgical practice, along with its unfavourable and untreated complications. The Vranashopha is described as earlier phase of Vrana. Sushruta has mentioned detail description of inflammatory swelling under the heading of Vranashopha. Among the all-available treatment modalities for Vranashopha (Cellulitis), the Jalaukavacharana and Jalaukavacharana with Panchavalkala Pralepa is found to be more effective by considering its feasibility, adoptability, cost-effectiveness and curative results. Sushruta has mentioned Lepa for local application in the treatment of Vranashopha. Methodology: In this present study, Jalaukavacharana, which is one of the proven therapy for treatment of Vranashopha was compared with easily available drug Jalaukavacharana with Panchavalkala Pralepa, by its local application directly on Vranashopha, to find out its effectiveness. A total 70 patients were randomly selected and divided in two groups. Jalaukavacharana and Jalaukavacharana with Panchavalkala Pralepa was done in group A and group B respectively for once for 5 days and observations are noted on 1st, 3rd, 5th, 10th and 15th day and the result was assessed thoroughly on the basis of observation according to the specially designed proforma. Result: Jalaukavacharana with Panchavalkala Pralepa was found to be more effective in all the four criteria, low cost therapy and easily available throughout the year. Conclusion: it was concluded that Jalaukavacharana with Panchavalkala Pralepa shown significant improvement in reducing pain, swelling, redness, local temperature and healing of wound at affected site without any side effect. Hence, it can be concluded that this Pralepa is useful in the treatment of Vranashopha (Cellulitis).